Developing a Harvest Plan by Considering the Effects of Skidding Techniques on Forest Soil Using a Hybrid TOPSIS-Entropy Method - Özer Genç, Çiğdem; Arıcak, Burak (Springer Science and Business Media LLC, 2022)
Abstract The aim of this study was to evaluate skidding techniques, which result in minimal damage to the soil, depending on the slope and stand type. Thus, three skidding techniques with tractor for harvesting (suspended skidding [SS], using a skidding cone [SC], and cable-pulling [CP]) were used in six different study sites and the variations in soil properties were examined at three different slopes (0%–20%, 20%–33%, >33%), 2 different stand types (A, B), and 2 different soil depths (0–5 cm, 5–10 cm). Soil bulk density, soil organic matter, soil compaction, organic carbon (C), and total nitrogen (N) were determined. The Entropy and TOPSIS methods were used among the multiple-criteria decision-making methods for six different coniferous stands. With the combination of the Entropy and TOPSIS methods, we found that slope was an important factor in determining the preferred skidding technique. Suspended skidding was seen as the preferred method of skidding technique in the 0–20% slope group. For the 20%–33% slope group, the usability of the three methods varied depending on stand type and soil depth, whereas the technique using a skidding cone was found to be the preferred skidding technique in the > 33% slope group.
Keywords: 15. Life on land